Participatory Pedagogy. Education vs. Pedagogy - Arkadiusz Żukiewicz (Studia z Teorii Wychowania)
The book by Martha Ann Davis McGaw and Simone McGaw-Evans: Participatory Pedagogy.Emerging Research and Opportunities, published by IGI Global, Hershey, Pennsylvania, USA (2020, ps. 156), deserves to be recommended to Polish readers for both formal and cognitive reasons. The title of the monograph may be an impulse for formal changes in the sphere of translating the category of pedagogy into English. In particular, it concerns the English translation of pedagogy consistent with the ontological essence of this science and the Polish tradition of pedagogical practice. The content of the book can, in turn, be an impulse and at the same time a kind of signpost in the search for effective solutions for school, educational and educational activities in the twenty-first century. The content of the book can, in turn, be an impulse and at the same time a kind of signpost in the search for effective solutions for school and pedagogical activities (including care and child-rearing – upbringing) in the twenty-first century.